Performance of the Salt Bridge Based Microbial Fuel Cell - Khan, Maksudur R.; Bhattacharjee, Ripon; Amin, M. S. A. (Science Publishing Corporation, 2012)
Electricity generation from readily biodegradable organic substrates accompanied by decolorization of azo dye was investigated using a Microbial fuel cell (MFC). Biodegradation was the dominant mechanism of the dye removal, and glucose was the optimal substrate for Red Cibacron-2G (RC) decolorization. Batch experiments were conducted to evaluate the performance of the MFC. As compared to traditional anaerobic technology higher decolorization efficiency was achieved by MFC. Effect of initial dye concentration and external resistance on power generation were studied. Polarization experiments were also directed to find the maximum power density. Maximum Power density of 100mW/m2 (1.04A/m2) was recorded at optimum operating conditions.